Terrorism and Economic Growth - Lassoued, Tahar; Hamida, Arafet; Hadhek, Zouhaier (International Journal of Economics and Financial Issues, 2018)
The objective of this research is to study the effect of terrorism on economic growth and the mechanisms of transmission of this effect. To do this, a model of simultaneous equations was applied to panel data for a sample of eleven countries (six developing and five developed) over the period 2008-2015. The findings of this study show the following: a positive effect of terrorism on economic growth for the whole sample as well as for the case of developing countries; a negative effect of economic growth on terrorism for the case of the total sample and the case of developing countries; and a negative effect of unemployment on terrorism for all the country samples. Furthermore, the study finds that people living in rural areas tend to engage more in terrorism that those of urban areas. Keywords: Terrorism, Economic growth, Simultaneous equations. JEL Classifications: C33, O47, N40